Planejamento ambiental como base ao plano diretor do campus da UFSM RS. - Valentini, Daiane Regina (2010)
The occupation in inadequate sites, the degradation of the natural resources, of the landscapes, it s brought to the reality of the Campus of UFSM in Santa Maria - RS, an unsustainable environmental situation ecological and partner-economically. Besides significant losses of the ecological biodiversity, the Campus presents mobility problems and urban infrastructure. Leaving of that reality, that work had for objectives to know, to analyze and gerency the environmental reality of the campus, adopting a ecosystem vision of the environment, through the integration of the urban, agricultural and natural ecosystems. Seeking to contribute for this purpose, the conceptual bases of the environmental planning were adopted proposed by Franco (2001). Para that, to map and systematic administration of the environmental reality of the Campus were accomplished starting from a Geographical System of Information (SGI), associated to the environmental analysis for geoprocessing, as methodology proposed by Xavier of Silva (1999) and Mello Filho (2003). In that way, in the Diagnosis Proceeding, the environmental data were organized in three class - Half Partner-cultural, Half Biotic and Half Physical-environmental, and these were analyzed and integrated through Environmental Evaluations. The Environmental Evaluations made use of add to of information, with space definitions of the reality and of the demands of the environmental legislation. As results were several identified potentials and environmental conflicts. As potentials stand out the several areas that shelter significant copies of the regional biota, the natural landscape, the low steepness of the ranch that facilitates the urban occupation, among others. At the same time, it is observed that the principal existent environmental conflicts meet in the irregularly occupation in APPs, mainly the urban occupations (constructions) and the areas cultivated for agricultural production. The Prognostics Proceeding, composed by the Environmental Zoning and the Strategies for the Environmental Administration they contemplate relative factors to the creation of a gradual process of preservation and recovery environmental ally to the improvement of the life conditions and urban development in the Campus. With certainty that study contributes to effective actions in the area of the process of Institutional Administration, presupposed necessary to the construction of a process of continuous Environmental Planning, of collective interest, participant and sustainable.